(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Study of sixteen elements microstrip array antenna of rectangular patches which is printed on the RT-duroid substrate, is presented in this paper. Air- Gap technique is used in this array configuration for the enhancement of Bandwidth. To study the bandwidth enhancement the radiation patterns have been plotted for E-plane, H-plane and array geometry. A precise comparison of radiation parameters of this array antenna are also performed with the same array antenna configuration without using Air-Gap technique. This Air-Gap bandwidth enhancement technique has provided around 62% enhancement. This technique is quite easy in implementation and make antenna structure very light weighted and handy essential for portable devices.